Analisis Pemasaran Sawi Hijau di Desa Balun Ijuk Kecamatan Merawang Kabupaten Bangka ( Studi Kasus Kelompok Tani Sepakat Maju) - Helda, Eva; Sundari, Desy; Antoni, Mirza (Universitas Bangka Belitung, 2008)
There are three channels in marketing of mustard at the farmer group of Sepakat Maju in Balun Ijuk, Merawang sub district. First, channel A is from merchant of village trader, then to retailer. Second, channel B is from merchant of sub district, then to retailer, and channel C is from merchant of district collecting trader, then to retailer. The biggest margin in marketing of channel A belongs to the retailer, that is Rp.1.500/kg. Merchant of village trader is about Rp.1.000/kg, and the smallest one belongs to the district merchant about Rp.500/kg. At channel B, the biggest margin belongs to a retailer that is Rp.1.500/kg, and the smallest one is for sub district merchant about Rp.1000/kg. At channel C, the biggest margin belongs to retailer about Rp.2.000/kg and the smallest is district merchant about Rp.1.000/kg. The most efficient channel in marketing mustard is channel A, belongs to the merchant of district about 0,01. Efficient channel in marketing mustard is channel A, belongs to the merchant of district about 0,01, artinya semakin angkanya mendekati 0 maka saluran pemasaran tersebut semakin efisien. Keyword : Marketing, Mustard, Bangka.